Cardiac effects of quinidine on guinea-pig isolated perfused hearts after in vivo quinidine pretreatment - Yang, Quan (1997)
1. Experimental and clinical studies suggest that class I and class III antiarrhythmic drugs may be subject to pharmacological tolerance during long term treatment, leading to loss of therapeutic effectiveness. 2. The aim of this study was to ascertain whether prolonged in vivo treatment with the Class Ia agent quinidine can modify cardiac (electrical and mechanical) responses to the drug. 3. A group of guinea-pigs (n=7) were treated intraperitoneally (q.d.) for 6 days with 75 mg kg(−1) quinidine sulphate. Preliminary pharmacokinetic experiments indicated that this dose could attain plasma concentrations similar to those that are therapeutic in man (2–5 mg l(−1)). A control group (n=7) received a saline solution for the same period. 4. Twenty-four hours after the last administration hearts were removed and retrogradely perfused at constant flow (stimulation frequency: 2.5 Hz). The following parameters were measured: maximal derivative of intraventricular pressure (dP/dt(max)); coronary perfusion pressure (Cp); PR, QRS and JT intervals, on surface ECG. The effects of quinidine on these parameters were measured at different concentrations (2, 4, 8, 12, 16, 20 μM) and compared in the two experimental groups. 5. In the control group quinidine decreased in a dose-dependent manner dP/dt and increased PR and QRS intervals. JT interval was increased at the lowest concentrations and decreased at the highest (biphasic effect). Cp did not change significantly. 6. In the pretreated group quinidine qualitatively produced the same effects on dP/dt and ECG intervals as in control group. Also the magnitude of these effects was not significantly different between the two groups. In contrast with findings in control experiments, Cp was significantly decreased by increasing quinidine concentration. Mean baseline Cp was higher in pretreated than in the control group (though not significantly, P=0.072) and quinidine addition abolished this difference. Thus, it is suggested that quinidine withdrawal induced a rebound increase in coronary tone, due to the unmasking of vasoconstrictor homeostatic mechanisms elicited by the in vivo vasodilating effect of the drug. 7. In conclusion, our data do not support the possibility that tolerance ensues during long term quinidine treatment, at least as far as electrophysiological and contractility effects are concerned. Further experimental work is needed to explain the appearance of a coronary vasodilating effect in pretreated hearts.